2020
DOI: 10.1080/09540105.2020.1754345
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo functional characterization of an immune activation Flammulina velutipes polysaccharide based on gut microbiota regulation

Abstract: Flammulina velutipes contains bioactive polysaccharides that can activate the immune system. Here we report the functional characterization in an immunomodulatory F. velutipes polysaccharide (FVP) both in vitro and in vivo. In cell experiment, FVP was discovered to be an activator to induce the M1polarization of the RAW 264.7 cells. In animal experiment, FVP was found to raise the gene expression of IL-1β, iNOS and ZO-1 in mice colon tissue. Moreover, it seemed to achieve the immune regulative function by rais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Liang obtained two polysaccharides CHFVP-1 (24.44 kDa) and CHFVP-2 (1,497 kDa) from F. velutipes and found that CHFVP-1 had procoagulant activity in vitro (12). A review of the literature shows that F. velutipes polysaccharides can modulate the intestinal microbiota of healthy mice and has potential immunomodulatory abilities (13,14). However, the target proteins of immunomodulatory effects of this biologically active polysaccharide in immunocompromised mice remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Liang obtained two polysaccharides CHFVP-1 (24.44 kDa) and CHFVP-2 (1,497 kDa) from F. velutipes and found that CHFVP-1 had procoagulant activity in vitro (12). A review of the literature shows that F. velutipes polysaccharides can modulate the intestinal microbiota of healthy mice and has potential immunomodulatory abilities (13,14). However, the target proteins of immunomodulatory effects of this biologically active polysaccharide in immunocompromised mice remains to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Species from the genus Akkermansia are often regarded as the gatekeepers of the intestinal mucosa and are known to assist the host against obesity and to improve intestinal health and host immunity. 40 Administration of mushroom polysaccharides from G. lucidum to mice fed a high-fat diet 32 and Flammulina velutipes to mice fed a standard diet 41 has been shown to increase the relative abundance of Akkermansia muciniphila in the intestine of these mice, which, in turn, positively regulated their immunity. Surprisingly, instead of restoring the relative abundance of the genus Akkermansia, P. sajor-caju supplementation reduced its population further, even though liver steatosis and inflammation in these rats was significantly reduced.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Administration of mushroom polysaccharides from G. lucidum to mice fed a high-fat diet and Flammulina velutipes to mice fed a standard diet has been shown to increase the relative abundance of Akkermansia muciniphila in the intestine of these mice, which, in turn, positively regulated their immunity. Surprisingly, instead of restoring the relative abundance of the genus Akkermansia, P.…”
Section: Discussionmentioning
confidence: 99%